Increasing Awareness of Renewable Energy for a Better Life for the Indonesian Migrant Worker Community in Penang Malaysia - Galang Persada Nurani Hakim; Mudrik Alaydrus; Umaisaroh Umaisaroh (Journal of Innovation and Community Engagement, 2024)
A community service team from Universitas Mercu Buana made a project initiative to increase the awareness of renewable energy for the Indonesian migrant worker community in Penang Malaysia. The goal of this project is to raise community awareness of environmental issues in response to providing a better life for Indonesian migrant workers. The primary goal is to establish sustainable behaviors and to encourage community involvement, especially among Indonesian migrant workers abroad. Through the use of a participatory strategy, the involvement included skill-sharing sessions and awareness campaigns. This needed to be done in order to make the community feel responsible for their action and aim for a better environment, hence a better life. The foundation of the approach was built on cooperative partnerships with each stakeholder that encouraged shared accountability. The results showed that the Indonesian migrant worker community's awareness had significantly increased, which resulted in the adoption of eco-friendly behavior. To validate the renewable energy transfer knowledge, the team then applied a questionnaire, especially question no.8 quoted “The community really feels the benefits of the community service program provided”. Using this method the team accumulated 93.75% satisfaction that renewable energy transfer knowledge has increased the knowledge and awareness of renewable energy among the participants of Indonesian Migrant Workers in Penang, Malaysia.